PTPRM Is Critical for Synapse Formation Regulated by Zinc Ion - Mo, Xiaoqiang; Liu, Mengxue; Gong, Jihong; Mei, Ying; Chen, Huidan; Mo, Huajun; Yang, Xiaofei; Li, Jun (Frontiers in Molecular Neuroscience, 2022)
In the nervous system, the trace metal ion zinc is required for normal mammalian brain development and physiology. Zinc homeostasis is essential for the control of physiological and pathophysiological brain functions. Synapses, the junctions between neurons, are the center of the brain’s information transmission. Zinc deficiency or excess leads to neurological disorders. However, it is still unclear whether and how zinc ion regulates synapse formation. Here, we investigated the effect of zinc on synapse formation in a cultured neuron system, and found that synapse formation and synaptic transmission were regulated by zinc ions. Finally, we identified that PTPRM is the key gene involved in synapse formation regulated by zinc ions. This study provides a new perspective to understanding the regulation of brain function by zinc ion.